Integrating customer-based brand equity and the theory of planned behavior to predict electric vehicle adoption in China: The moderating role of perceived price - Chuan Zheng; Danling Sun; Munirah Khamarudin; Azanin Ahmad; Han Wei; Jie Xu (PLoS ONE, 2025)
Despite burgeoning global sustainability efforts, the widespread adoption of electric vehicles (EVs) in China faces persistent hurdles, highlighting a critical need to unravel the intricate psychological and brand-related factors that drive consumer purchase decisions. This pioneering study addresses this gap by innovatively integrating customer-based brand equity (CBBE) with the robust theory of planned behavior (TPB), offering a comprehensive framework to predict EV adoption. Drawing on responses from 379 potential EV consumers across six major cities in China, this research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. A two-stage analytical strategy is adopted—validating the measurement model, followed by a rigorous assessment of structural paths including direct, mediating, and moderating relationships among key constructs. Results reveal that all four CBBE components—brand awareness, brand association, perceived quality, and brand loyalty—significantly influence attitude, confirming their critical role in shaping consumer perceptions. The findings demonstrate that attitude, perceived behavioral control, brand association, perceived quality, and brand loyalty significantly influence purchase intention, while subjective norms and brand awareness show no direct effect. Mediation analysis confirms that attitude partially mediates the effects of brand association, perceived quality, and brand loyalty on purchase intention, but not brand awareness. Furthermore, perceived price negatively moderates the relationship between attitude and purchase intention. This research offers groundbreaking insights into brand equity and consumer psychology’s role in accelerating EV adoption. This model provides unprecedented theoretical contributions by linking CBBE and TPB for sustainable consumption. For practitioners, it delivers actionable, evidence-based strategies enabling automakers and policymakers to significantly boost EV market penetration, forging a more sustainable future. This work is a powerful roadmap for unlocking the EV market’s full potential in China and globally.